2018
DOI: 10.26529/cepsj.426
|View full text |Cite
|
Sign up to set email alerts
|

School Buildings for the 21st Century: Some Features of New School Buildings in Iceland

Abstract: The aim of this study is to identify features of change in the recent design of school buildings in Iceland, and how they might affect teaching practices. Environmental and architectonic features characterising school buildings designed and built at the beginning of the 21st century are examined in light of challenges involving architecture, educational ideology, school policy and digital technology. The sample for the study consists of 20 schools located in four municipalities. Four of the school buildings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Building design in Europe similarly follows these national imperatives, with these open and flexible designs much more prevalent and currently preferred in some countries, such as the Nordic countries (see e.g. Grannäs and Stavem, 2020;Sigurðardóttir and Hjartarson, 2011), than in others, where enclosed classroom prevail even in new buildings (see e.g. Duthilleul et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Building design in Europe similarly follows these national imperatives, with these open and flexible designs much more prevalent and currently preferred in some countries, such as the Nordic countries (see e.g. Grannäs and Stavem, 2020;Sigurðardóttir and Hjartarson, 2011), than in others, where enclosed classroom prevail even in new buildings (see e.g. Duthilleul et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Woolner et al (2018), compelling research demonstrates that different physical configurations facilitate some paedagogical approaches while hindering others. Sigurðardóttir and Hjartarson (2011) in a study of new school buildings in Iceland found evidence that teachers were more likely to collaborate in open-plan classrooms and that students had more choice in the tasks they chose, while open-plan schools foster student involvement, teacher cooperation, collaboration and, often, team-teaching. However, Saltmarsh et al (2015) argue that open-plan classrooms cause considerable pedagogic challenges for teachers.…”
Section: The School Design Contextmentioning
confidence: 99%
“…Barret et al, 2019, reporting for the World Bank) and extensive investment in educational infrastructure in many countries (EC interim paper, 2022), there is enthusiasm for Innovative Learning Environments -ILEs. This interest includes research and policy papers from the OECD (OECD, 2013; and school building programs centering on particular, innovative, open and flexible designs (Bradbeer et al, 2017;Niemi, 2021;Sigurðardóttir & Hjartarson, 2011). The intention is that schools built to these designs that provide variation in the type of spaces available 2 can support a wider range of pedagogies, teaching and learning activities and student groupings.…”
Section: The Potential Of Innovative Educational Spacementioning
confidence: 99%
“…The intention is that schools built to these designs that provide variation in the type of spaces available 2 can support a wider range of pedagogies, teaching and learning activities and student groupings. These aspects are often seen as enabling individualized or personalized learning, where the teaching staff can respond to each student's particular learning needs (Sigurðardóttir & Hjartarson, 2011). Another key, underpinning, intention of these designs is to promote student autonomy by enabling more student directed learning through providing scholars with more choice about how and where they engage with learning activities (Carvalho & Yeonman, 2018; for a thoughtful discussion on the relationship between innovative learning and alternative forms of school architecture, see Schabmann et al, 2016).…”
Section: The Potential Of Innovative Educational Spacementioning
confidence: 99%